Optimizing New Student Data Collection: Study of the Implementation of the Dapodik Application at SMA Negeri 1 Porong - Isnaini Rodiyah; Hendra Sukmana; Isna Fitria Agustina; Winda Fitri Lestari (Research Parks Publishers, 2021)
This research analyzes the implementation of Basic Education Data (DAPODIK) at SMA Negeri 1 Porong in the context of optimizing data, with a focus on the role of bureaucratic structure, availability of resources, and effectiveness of collaboration between parties. Using a qualitative approach with a case study method, data was collected through semi-structured interviews and documentation analysis. Data analysis uses George Edward III's theoretical framework, which highlights the importance of communication, resources, disposition and bureaucratic structure in the implementation of public policy. The findings show that a well-defined bureaucratic structure, with clear SOPs and effective coordination, supports the smooth implementation of DAPODIK. The availability of competent human resources is also an important factor. The main challenges are limited ICT infrastructure and the need to increase active participation from students and parents. This research underlines the importance of regular evaluation and adaptation of implementation strategies to ensure the effectiveness of DAPODIK in supporting and improving the quality of education.